Karakterisasi Kromosom Spesies Anggota Familia Solanaceae - Ganies Riza Aristya; Chalvia Zuyyina; Dea Febiansi; Rifa Ayuningsih; Kusnah Dian Prasiwi; Triska Ayu Nurwijayanti; Uswatun Mujahidah; Bartolomius Renaldy (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
Indonesia is known as a country rich in various agricultural and plantation products, including vegetables. One effort to improve quality of the production by identifying and characterizing chromosomes. The purpose study to characterize number, shape and size of the chromosomes in Solanaceae family. The study using modified Squash method. Chromosome preparation including fixation, maceration, staining, and analyzed using Image Raster 3 application, then Corel Draw X6. The results showed study to characterize the number, shape and size in the Capsicum annum L. Tm 999 (2n=20m+4sm and 2,41 s/d 9,99 µm) then Capsicum frutescens L. Kencana (2n=16m+8sm and 3,12 s/d 10,49 µm). In Solanum lycopersicum Or Diana and Marta (2n=16m+8sm and 3,12 s/d 10,49 µm) then (2n=22m+2sm and 2,65 s/d 7,28 μm). In Lycopersicon esculentum Mill. Juliet and Tropical Ruby (2n=18m+6sm and 0,77 s/d 1,81 μm) then (2n=20m+4sm and 0,39 s/d 0,94 μm). Solanum melongena L. Or Valerie and Mustang (2n=24m and 0.29 s/d 0.87 μm) then (2n=22m+2sm and 0,5 s/d 1.28 μm). In Solanum melongena L. Kania and Pulus (2n=20m+4sm and 0.64 s/d 3.43 μm) then (2n=16m+8sm and 0.84 s/d 2.51 μm). In Solanum melongena L. Jeno and Planet Hijau (2n=18m+6sm and 0.65 s/d 2.423 μm) then (2n=14m+10sm and 0.46 s/d 1.73 μm). In Capsicum annum var. Grossum L. Red Star and Purple Star (2n=22m+2sm and 3.19 s/d 8.49 μm) then (2n=24m and 5.5 s/d 11.92 μm).